Inscribing the victor's land: nationalistic authorship in Sri Lanka's post-war Northeast. Issue 5 (2nd September 2016) - Seoighe, Rachel
Abstract: This article examines the nationalistic authorship of space in Sri Lanka's post-conflict Northeast as part of the state's nation-building strategy and as a continuation of a post-colonial process of Sinhala-Buddhist nationalistic revival. Exploring issues of historiography, conflict resolution, physical vehicles of ideology and collective memory, the article demonstrates how land policies, development and the tourism industry in a post-conflict context can go hand-in-hand with dispossession, militarisation and the humiliation of a 'defeated' minority community.